Edukasi Diet Rotasi Eliminasi Berbasis Website Berpengaruh Terhadap Pengetahuan Ibu dan Pola Konsumsi Anak Autisme - Fajri, Muthiah Syafiqoh; Moviana, Yenny; Suparman, Suparman; Surmita, Surmita (Jurusan Gizi Poltekkes Kemenkes Bandung, 2023)
Autism is a disorder diagnosed with a breakdown in lead social relationships, a breakdown in communication, and a lack of interest in behaving and developing skills. Website Carrd.co is a website platform that can be developed for free, with interesting displays, and easy to use for newbies. This research used a pre-experimental design with the pre-post test. The research was conducted in March-April 2023 at SLB Negeri 2 Sentra PK/PLK and SLB C Tut Wuri Handayani. The respondents of this research were 12 people who were determined by total sampling. The data collected included characteristic respondents, mother’s knowledge, children’s nutrient intake, and children's eating frequency. The intervention was measured using a knowledge questionnaire and Semi Quantitative Food Frequency Questionnaire (SQ-FFQ). The normality test uses the Shapiro Wilk test, and the analysis test uses the Paired T-Test Dependent (data normally distributed) and the Wilcoxon Test (data not normally distributed). The results showed that there were significant differences in the average knowledge of mothers (p value 0.026), children's energy intake (p value 0.004), children's protein intake (p value 0.001), children's fat intake (p value 0.001), children's carbohydrate intake (p value 0.005), and the frequency of children's eating (p value 0.025) before and after the intervention. The use of motivational interviewing methods in providing nutrition education can increase changes in consumption behavior of mothers towards children with autism.